The False «Reform» of the Regulations on Public Procurement: Intuitions, Uncertainty and Vagueness - Effio Ordoñez, Augusto (2015)
In the present article, the author shows his critical position about the reform of the regulatory framework on public procurement matter.Parting from some relevant aspects of the law, he explains the reason why he considers that this reform seems to lack of motivation and an adequate consideration of the actual status of public procurement in our country, calling into question the fact that we are facing a real reform.